Estimating the gap between demand and supply of medical appointments by physicians for hypertension care: a pooled analysis in 191 countries. Issue 4 (4th April 2022) - Carrillo-Larco, Rodrigo M; Guzman-Vilca, Wilmer Cristobal; Neupane, Dinesh
Abstract : Introduction: With a growing number of people with hypertension, the limited number of physicians could not provide treatment to all patients. We quantified the gap between medical appointments available and needed for hypertension care, overall and in relation to hypertension treatment cascade metrics. Methods: Ecological descriptive analysis. We combined country-year-specific data on hypertension prevalence, awareness, treatment and control (from Non-Communicable Disease Risk Factor Collaboration) and number of physicians (from WHO). We estimated from 1 to 12 medical appointments per year for patients with hypertension. We assumed that physicians could see 25 patients per day, work 200 days/year and dedicate 10% of their time to hypertension care. Results: We studied 191 countries. Forty-one countries would not have enough physicians to provide at least one medical appointment per year to all the population with hypertension; these countries were low/lower middle income and in sub-Saharan Africa or East Asia and Pacific. Regardless of the world region, ≥50% of countries would not have enough physicians to provide ≥8 medical appointments to their population with hypertension. Countries where the demand exceeded the offer of medical appointments for hypertension care had worse hypertension diagnosis, treatment and control rates than countries where the demand did not exceed the offer. There were positive correlations between the physician density and hypertension diagnosis (r=0.70, p<0.001), treatment (r=0.70, p<0.001) and control (r=0.59, p<0.001). Conclusions: Where physicians are the only healthcare professionals allowed to prescribe antihypertensive medications, particularly in low and middle-income countries, the healthcare system may struggle to deliver antihypertensive treatment to patients with hypertension.